The flow design of information a good site, navigation maps, with Macromedia Dreamweaver MX 6.0 - author author (Jurnal Sistem Informasi, 2005)
In scientific writing, the author only restrict the flow of planning information, guidance on good sites, map navigation, the formation of elements, creating web pages, Macromedia Dreamweaver MX 6.0 on web pages together with HTML tags, making the link with the text and test Web pages with Microsoft Internet Explorer. The objective is that companies can more easily. And increased satisfaction with the pelangganya, also became a benchmark to assess to which the writer's ability, improve information quickly and accurately. Is organized, not too hard to read, but still have a professional design and can be updated on a regular basis, so that accessing and communicating accurate information can be received with interactive, efficient, and fast for a person's job satisfaction. For this writing the author tried: Introducing MacromediaDreamweaver MX 6.0 to create web pages (web site) personal, Implementing a web page (web site) that has been made, Focusing on the design of writing interactive web pages, effectively and efficiently in accordance with the profile of personal homepage, so by the company could run faster than before. Because all products will be marketed through the web more easily recognized by consumers.